evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - SONG, HUI-XING; GAO, SU-PING; JIANG, MING-YAN; LIU, GUANG-LI; YU, XIAO-FANG; CHEN, QI-BING (Journal of genetics, 2012)
Ribosomal internal transcribed spacer (ITS) sequences are commonly used for phylogenetic reconstruction because they are highly reiterated as components of rDNA repeats, and hence are often subject to rapid homogenization through concerted evolution. Concerted evolution leads to intragenomic uniformity of repeats even between loci on nonhomologous chromosomes. However, a number of studies have shown that the ITS polymorphism within individuals is quite common. The molecular systematics of Bambusinae and related species were recently assessed by different teams using independently generated ITS sequences, and the results disagreed in some remarkable features. Here we compared the ITS sequences of the members of Bambusa s. l., the genera Dendrocalamus, Dinochloa, Gigantochloa, Guadua, Melocalamus, Monocladus, Oxytenanthera, Thyrsostachys, Pleioblastus, Pseudosasa and Schizostachyum. We have reanalysed the ITS sequences used by different research teams to reveal the underlying patterns of their different results. After excluding the sequences suspected to represent paralogous loci, a phylogenetic analysis of the subtribe Bambusinae species were performed using maximum parsimony and maximum-likelihood methods. The implications of the findings are discussed. The risk of incorporating ITS paralogues in plant evolutionary studies that can distort the phylogenetic signal should caution molecular systematists.